Association of Patient Experience With Guideline-Concordant Colon Cancer Treatment in the Elderly. Issue 6 (June 2021) - Snyder, Rebecca A.; Wardrop, Rebecca; McLain, Alexander C.; Parikh, Alexander A.; Cass, Anna L.
Abstract : PURPOSE: The association between patient-reported experience of care and care quality is not well described. The purpose of this study was to assess the relationship between the patient-reported experience and receipt of guideline-concordant colon cancer (CC) treatment. METHODS: Medicare beneficiaries with resected stage I-III CC (2003-2013) were identified in the linked SEER Consumer Assessment of Healthcare Providers and Systems data set. Patient-reported scores were compared by receipt of guideline concordant care (GCC) (resection of ≥ 12 lymph nodes [stage I-III] and adjuvant chemotherapy [stage III]). Linear mixed-effects regression was performed to compare adjusted mean patient experience scores by GCC. RESULTS: Of the 1, 010 identified patients, 58.4% of stage I (n = 192/329) and 73.4% of stage II (n = 298/406) patients underwent resection of ≥ 12 LN. Among stage III patients, 76.0% (n = 209/275) underwent resection of ≥ 12 lymph node and 52.4% (n = 144/275) received adjuvant chemotherapy. By multivariable analysis, patient-reported scores of healthcare quality, physicians, physician communication, getting needed care, and getting care quickly were similar among patients who received GCC compared with those who did not. However, mean scores of overall healthcare quality (91.3 v 82.4, P = .0004) and getting needed care (92.8 v 86.8, P = .047) were higher among stage III patients who received GCC compared with those who did not. CONCLUSION: Patient-reported scores of healthcare quality and ability to get needed care are associated with GCC among elderly patients with stage III CC. Further investigation is needed to determine whether patient-reported experience correlates with other clinical measures of quality of CC care.